The chromatin landscape at the HIV-1 provirus integration site determines viral expression - Vansant, Gerlinde; Chen, Heng-Chang; Zorita, Eduard; Trejbalová, Katerina; Miklík, Dalibor; Filion, Guillaume; Debyser, Zeger (Nucleic acids research, 2020)
HIV-1 persists lifelong in memory cells of the immune system as latent provirus that rebounds upon treatment interruption. Therefore, the latent reservoir is the main target for an HIV cure. Here, we studied the direct link between integration site and transcription using LEDGINs and Barcoded HIV-ensembles (B-HIVE). LEDGINs are antivirals that inhibit the interaction between HIV-1 integrase and the chromatin-tethering factor LEDGF/p75. They were used as a tool to retarget integration, while the effect on HIV expression was measured with B-HIVE. B-HIVE tracks insert-specific HIV expression by tagging a unique barcode in the HIV genome. We confirmed that LEDGINs retarget integration out of gene-dense and actively transcribed regions. The distance to H3K36me3, the marker recognized by LEDGF/p75, clearly increased. LEDGIN treatment reduced viral RNA expression and increased the proportion of silent provirus. Finally, silent proviruses obtained after LEDGIN treatment were located further away from epigenetic marks associated with active transcription. Interestingly, proximity to enhancers stimulated transcription irrespective of LEDGIN treatment, while the distance to H3K36me3 only changed after treatment with LEDGINs. The fact that proximity to these markers are associated with RNA expression support the direct link between provirus integration site and viral expression.
Keywords: Proviruses; proviry; chromatin; Intercellular Signaling Peptides and Proteins; regulace exprese virových genů; Gene Expression Regulation, Viral; lidé; HIV Integrase Inhibitors; HIV-1; Cell Line; RNA, Viral; Chromatin; integrace viru; umlčování genů; Virus Integration; Gene Silencing; buněčné linie; RNA virová; histony; inhibitory HIV-integrasy; mezibuněčné signální peptidy a proteiny; Humans; Histones